1992
DOI: 10.1017/s0022112092001009
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy- and thermocapillary-driven flows in differentially heated cavities for low-Prandtl-number fluids

Abstract: The influence of thermocapillary forces on buoyancy-driven convection is numerically simulated for shallow open cavities with differentially heated endwalls and filled with low-Prandtl-number fluid. Calculations are carried out by solving two-dimensional Navier-Stokes equations coupled to the energy equation, for three aspects ratios A = (length/height) = 4, 12.5 and 25, and several values of the Grashof number (up to 6 × 104) and Reynolds number (|Re| ≤ 1.67 × 104). Thermocapillarity can have a quite signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…It can be seen that the curve does not intersect the Gr = 0 line at any point. This is consistent with both the steady and unsteady results calculated by Mundrane & Zebib [7], Ben Hadid & Roux [11].…”
Section: Combined Buoyancy-and Thermocapillary-driven Flows For a =supporting
confidence: 92%
“…It can be seen that the curve does not intersect the Gr = 0 line at any point. This is consistent with both the steady and unsteady results calculated by Mundrane & Zebib [7], Ben Hadid & Roux [11].…”
Section: Combined Buoyancy-and Thermocapillary-driven Flows For a =supporting
confidence: 92%
“…The boundary layer scalings for buoyant and thermocapillary convection have been established well Carpenter and Homsy (1989). Then, Hadid and Roux (1992) analyzed a shallow cavity and showed that surface tension can have a quite significant effect on the stability of a primary buoyancy driven flow. Effects of a magnetic field on the combined convection were studied by Rudraiah et al (1995) and Hossain et al (2005).…”
Section: Introductionmentioning
confidence: 96%
“…Carpenter and Homsy [6] established the boundary layer scalings for the buoyant and thermocapillary convection. Hadid and Roux [7] analyzed a shallow cavity, and showed that the surface tension had a quite significant effect on the stability of a primary buoyancy driven flow. Rudraiah et al [8] and Hossain et al [9] studied the effects of a magnetic field on the combined convection.…”
Section: Introductionmentioning
confidence: 99%